Exploration of Ecoliteracy Values ​​in the Aruh Tradition of Loksado Village as a Source of Social Studies Learning Based on Local Wisdom - Sovia Husni Rahmia; Fatwa Nur'aini; Muhammad Imam Hulaimi; Rusmaniah Rusmaniah; Syarifuddin Syarifuddin (Indonesian Journal of Social Science Education (IJSSE), 2026)
Environmental issues in the 21st century are increasingly complex, requiring systematic and integrated efforts to raise ecological awareness through education. Environmental education based on local wisdom offers a contextually relevant alternative, particularly in social studies learning, which has long struggled with content that is overly theoretical and disconnected from students' daily realities. This study aims to explore the ecoliteracy values embedded in the Aruh tradition in the Loksado Village community and analyze its potential as a resource for local wisdom-based social studies learning. Unlike previous studies that examined the Aruh tradition primarily from a social and cultural perspective, this study specifically connects its ecological dimensions to a social studies learning framework, addressing a gap in the literature on locally rooted ecoliteracy in social studies education. A qualitative case study method was used, with data collected through in-depth interviews with traditional leaders, social studies teachers, and community members, participant observation during the Aruh ritual cycle, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, with credibility ensured through triangulation of sources and techniques. The findings indicate that the Aruh tradition embodies comprehensive ecoliteracy values across five dimensions: simple living in harmony with nature, environmental awareness, natural resource conservation, ecological rest practices, and compassion for living things. These values align with Social Studies Learning Outcomes (CP) 1 and 2 Phase D, particularly on the topics of the local environment, natural resource conservation, and sustainable development. Integrating the Aruh tradition as a social studies learning resource has strong potential not only to deepen students' conceptual understanding but also to foster ecological awareness and strengthen local cultural identity. Further studies are recommended to develop and test learning modules based on this tradition.